Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3389/fpls.2022.1019512
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of a novel strain of Bacillus halotolerans protecting wheat from sheath blight disease caused by Rhizoctonia solani Kühn

Abstract: Rhizoctonia solani Kühn naturally infects and causes Sheath blight disease in cereal crops such as wheat, rice and maize, leading to severe reduction in grain yield and quality. In this work, a new bacterial strain Bacillus halotolerans LDFZ001 showing efficient antagonistic activity against the pathogenic strain Rhizoctonia solani Kühn sh-1 was isolated. Antagonistic, phylogenetic and whole genome sequencing analyses demonstrate that Bacillus halotolerans LDFZ001 strongly suppressed the growth of Rhizoctonia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 82 publications
0
0
0
Order By: Relevance
“…In the sheath blight control experiment with BG-2, it was found that BG-2 had a notable control effect on the occurrence of maize sheath blight [44] (Figure 5). A new bacterial strain, Bacillus halotolerans LDFZ001, demonstrated efficient antagonistic activity against the pathogenic strain Rhizoctonia solani [92]. The Bacillus polymyxoides SF05 strain can also be utilized to control maize sheath wilt and induce systemic resistance [93].…”
Section: Biological Controlmentioning
confidence: 99%
“…In the sheath blight control experiment with BG-2, it was found that BG-2 had a notable control effect on the occurrence of maize sheath blight [44] (Figure 5). A new bacterial strain, Bacillus halotolerans LDFZ001, demonstrated efficient antagonistic activity against the pathogenic strain Rhizoctonia solani [92]. The Bacillus polymyxoides SF05 strain can also be utilized to control maize sheath wilt and induce systemic resistance [93].…”
Section: Biological Controlmentioning
confidence: 99%